Analisis pengetahuan siswa SMA dan SMK di Balikpapan Tengah: terkait mitigasi bencana tanah longsor - Muhammad Zidan Al Fiqri; Abdul Hakim Hamidi; Yuyun Kusmiati; Alika Putri; Andi Marini (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2025)
Landslide is a natural phenomenon that occurs when the movement of soil and rock on a slope takes place due to the influence of gravity, so that the material moves towards the surrounding lower area. In Indonesia, the incidence of landslides is quite high, and Balikpapan is one of the areas vulnerable to this disaster. This study aims to assess the understanding of high school students in Central Balikpapan regarding landslide disaster mitigation. To achieve this goal, the method used in this research is documentation study from various scientific journals to develop questions which are then distributed through Google Form as a database. The targeted respondents are high school and vocational school students in Central Balikpapan area. The results show that 97.20% of the students know the causes and characteristics of landslides, while the other 2.80% still do not know the causes and characteristics of landslides. These findings provide valuable insights for related institutions in landslide disaster mitigation efforts.